2020
DOI: 10.1002/saj2.20117
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of in‐season soil nitrogen concentration with corn yield and potential nitrogen losses

Abstract: New process‐based tools for predicting in‐season soil nitrogen (N) levels has the potential to provide timely information for N management decisions for corn (Zea mays L.) production systems in the U.S. There is, however, little published data supporting the assumption that soil mineral N (SMN, NH4‐N + NO3‐N at 0–60 cm) is correlated with yield response at different vegetative growth stages. Moreover, the degree to which changes in SMN influence the risk of N losses is uncertain. Data from 32 site‐years of fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
5
1
Order By: Relevance
“…Given the high indigenous soil N supply, even if small changes in cumulative soil N availability due to biochar were detected, this likely would not have caused nutrient deficiency. Previous work in Illinois has shown that lower soil N concentrations at key maize growth stages are associated with yield reductions, but the relative differences were much larger than observed in the current study (Preza Fontes et al., 2020). Thus, the lack of effects of biochar on maize yield and N uptake was not unexpected.…”
Section: Discussioncontrasting
confidence: 83%
“…Given the high indigenous soil N supply, even if small changes in cumulative soil N availability due to biochar were detected, this likely would not have caused nutrient deficiency. Previous work in Illinois has shown that lower soil N concentrations at key maize growth stages are associated with yield reductions, but the relative differences were much larger than observed in the current study (Preza Fontes et al., 2020). Thus, the lack of effects of biochar on maize yield and N uptake was not unexpected.…”
Section: Discussioncontrasting
confidence: 83%
“…Kramberger et al (2014) reported the association between high soil N balance values, low maize yields and low N uptake values in maize. In this study, the opposite was true, because it was in the treatments where the highest yields were obtained that we had the highest accumulated N values, the highest values in the soil N balance and also the highest % CNc supplied to the main crop, like in a study developed by (Preza-Fontes et al, 2020). These results evidence the positive effects of cover crops in supply N to succeeding crop.…”
Section: Tablementioning
confidence: 51%
“…The methods for conducting field experiments to monitor SMN over time have been previously reported by Banger et al [20] and Preza-Fontes et al [21]. Briefly, the database of SMN concentrations contained a total of 1149 observations collected from 32 site-years of N management studies conducted at research stations and on-farm trials across Illinois between 2015 and 2018 (Table A1 in Appendix A).…”
Section: Soil N Concentration Data Collection In Field Experimentsmentioning
confidence: 99%
“…Soil N concentrations were averaged across depths, resulting in SMN (sum of nitrate-N and ammonium-N) at 0-60 cm depth. The N management treatments consisted of 12 different combinations of N fertilizer rates, timing, and source, plus a control treatment with zero N (see Preza-Fontes et al [21] for a full description of N treatments). In addition to these treatments, the multiple locations across years created a range of SMN concentrations under different soil and weather conditions.…”
Section: Soil N Concentration Data Collection In Field Experimentsmentioning
confidence: 99%
See 1 more Smart Citation